Potentiation of Glibenclamide Hypoglycaemia in Mice by MK‐467, a Peripherally Acting Alpha2‐Adrenoceptor Antagonist. Issue 6 (30th July 2015) - Ruohonen, Suvi T.; Ranta‐Panula, Ville; Bastman, Sanna; Chrusciel, Paulina; Scheinin, Mika; Streng, Tomi
Abstract: Pharmacological antagonism and genetic depletion of pancreatic α2A ‐adrenoceptors increase insulin secretion in mice and enhance the insulinotropic action of glibenclamide, a representative of the sulphonylurea class of insulin secretagogues used in the therapy of type 2 diabetes. Antagonism of α2 ‐adrenoceptors in the central nervous system (CNS) causes tachycardia and hypertension, making generalized α2 ‐adrenoceptor blockade unfavourable for clinical use despite its potential to decrease blood glucose levels. The purpose of this study was to test the acute effects of the peripherally acting α2 ‐adrenoceptor antagonist MK‐467 alone and in combination with glibenclamide in non‐diabetic C57BL/6N mice. Cardiovascular safety was assessed in freely moving mice with radiotelemetry. Dose‐dependent decreases in blood glucose and increases in plasma insulin concentrations were seen with the combination of MK‐467 and glibenclamide; the combinations were much more potent than glibenclamide or MK‐467 alone. Furthermore, MK‐467 had no effect on mean arterial pressure or heart rate in freely moving mice and did not prevent the centrally mediated hypotensive effect of the α2 ‐adrenoceptor agonist medetomidine. Thus, peripheral blockade of α2 ‐adrenoceptors does not evoke the same cardiovascular adverse effects as antagonism of CNS α2 ‐adrenoceptors. The current results indicate that the combined use of small doses of a peripherally acting α2 ‐adrenoceptor antagonist with a sulphonylurea drug could provide a novel option for the treatment of type 2 diabetes, especially in patients with increased tonic α2 ‐adrenoceptor‐mediated inhibition of insulin secretion.